Detection of breathing and heartrate using a simple vital radio system - Gauni, Sabitha; T.Manimegalai, C; Kalimuthu, K; Anjanasree, M (International Journal of Engineering and Technology, 2018)
Proposed is a detection technique utilised for the physiological monitoring of heart rate and breathing rate. This new methodology is better than the other conventional systems that utilise either continuous waves or impulse radio systems for detecting remote vital signs that either suffers from non-stationary clutters or anomalies in accuracy. Vital Radio which operates on wireless technology can sense and monitor the breathing rate and the heart beat rate of the concerned person. This device is designed in such a manner that it can be installed in the walls so that it can capture and maintain a health record of a person dwelling in smart homes. It has the prime advantage of revealing high level of accuracy in the detection of the required vital signs.
Keywords: .